A 1D–3D interconnected δ-MnO2 nanowires network as high-performance and high energy efficiency cathode material for aqueous zinc-ion batteries. (20th February 2021) - Liu, Dao-Sheng; Mai, Yinglin; Chen, Shufeng; Liu, Sucheng; Ang, Edison Huixiang; Ye, Minghui; Yang, Yang; Zhang, Yufei; Geng, Hongbo; Li, Cheng Chao
Abstract: Aqueous zinc‐ion batteries (AZIBs) have received significant research attention and widely investigated because of their high intrinsic safety and cost effectiveness. Manganese dioxide has been regarded as a promising cathode material for AZIBs, attributed to its friendliness, abundant resources, high theoretical capacity, and high working voltage. Herein, a unique one-dimensional–three-dimensional (1D–3D) hybrid network with interconnected δ-MnO2 nanowires was reported as a cathode material for AZIBs. A distinctive 3D nano network structure resulted in enhancement of electrolyte osmosis and significant increase in contact between electrode and electrolyte, and also provided more active sites and convenient rapid ion transport routes. Moreover, the fine nanowire structure and the optimum layer spacing resulted in easier insertion/deinsertion of ion in the active material. Taking advantage of this feature, the δ-MnO2 cathode provides high reversible capacity, fast rate capability and good longevity for cycling. Further kinetic experiments revealed that Zn/δ‐MnO2 system constitutes an electrochemical reaction regulated by the combination of ionic diffusion and pseudo-capacitance; and shows high energy efficiency during the charge/discharge states. This research may provide an advanced cathode material for AZIB development.